The Oscillation on Solutions of Some Classes of Linear Differential Equations with Meromorphic Coefficients of Finite [p,q]-Order - Hong-Yan Xu; Jin Tu; Zu-Xing Xuan (The Scientific World Journal)
This paper considers the oscillation on meromorphic solutions of the second-order linear differential equations with the form f′′+A(z)f=0, where A(z) is a meromorphic function with [p,q]-order. We obtain some theorems which are the improvement and generalization of the results given by Bank and Laine, Cao and Li, Kinnunen, and others.